THE USE OF PARALLELISMS IN ABDULLA ORIPOV'S POEMS (TAMADDUN NURI JURNALI, 2024)
In world literature, the emphasis is growing on revealing the role and importance of artifacts in the development of poetry from a linguistic, pragmatic, linguistic point of view. The resulting embryo was allowed to develop in nutrients and then inserted into her womb, where it implanted. About the use and types of parallelisms in the analysis of some poems from the work of Abdulla Oripov